Comparing the accuracy of high tibial osteotomies between computer navigation and conventional methods. Issue 1 (1st January 2017) - Chang, Justin; Scallon, Greg; Beckert, Mitch; Zavala, Jeff; Bollier, Matthew; Wolf, Brian; Albright, John
Abstract: Background: The accuracy of correction has been shown to be an important determinant in long-term outcomes of patients who were treated with a medial open-wedge high tibial osteotomy (HTO) who suffer from unicompartmental osteoarthritis (OA). Computer navigation systems have the potential to improve surgical precision. The purpose of this study was to compare radiographic outcomes between patients treated with a navigation system and those treated through conventional methods of assessing alignment intra-operatively. The null hypothesis was that the method of assessing the alignment intra-operatively would make no difference in the accuracy of correction. Methods: In this retrospective study, 107 patients with medial varus OA who were managed by open-wedge HTO were included. Of the 107 patients, 41 were treated using an intraoperative navigation system and 66 were treated using conventional methods. Pre-operative and post-operative single-leg, long-leg standing alignment films were used to determine the extent of pre-operative varus deformity and the post-surgical correction achieved compared to the predetermined target range. Results: The navigational system had eight instances of software malfunction (19.5%) intra-operatively and correction was determined using the cable method. These results were analyzed as part of the conventional group. Post-operative radiographic differences were significant between the two groups. In the navigation group, 75.8% of the patients were corrected within the target range compared to 66.2% in the conventional group. More patients were also under corrected (to the point of remaining in varus) using conventional methods compared to a navigation system. There was no statistically significant difference in the degree of correction in the sagittal plane between the two groups. Regardless of the method used for checking alignment intra-operatively, there was a statistically significant difference in post-operative weight-bearing measurements when the surgeon had intra-operative axial loading versus when they did not. Conclusion: For coronal plane corrections, the navigation system was shown to have greater success in achieving the desired correction value and in having fewer patients who were under corrected. Despite the measurement technique a surgeon chooses to assess the accuracy of correction, axial loading the extremity in order to simulate the weight-bearing film alignment post-operatively is important to maximize the accuracy of correction needed.